Structural violence, social suffering, and the COVID-19 syndemic: discourses and narratives on the margins of the state in Texas - Dove, Sophia Annette; Khan, Shamshad; Kline, Kimberly N. (Frontiers in Communication, 2024)
While the repercussions of the novel Coronavirus or COVID-19 have been felt across the world over the past few years, the impact has not been consistent. Instead, it has been mediated by the systemic ways in which existing social and structural disparities have failed vulnerable populations globally. Drawing on document analysis and fifteen in-depth interviews (n=15) conducted among the key stakeholders in the city of San Antonio, South Central Texas, this paper reveals how structural violence worsened during the COVID-19 pandemic resulting in making it a syndemic pandemic of high rates of deaths and illnesses among the most vulnerable and disadvantaged groups. A grounded theory approach particularly revealed themes of social suffering such as low income and pre-existing medical conditions that contributed to higher mortality rates, the presence of racism and misinformation, the importance of trustworthy communication channels, and streamlined collaborative partnerships with clear and effective communication through all levels of the government, especially when communicating scientific information.